0086 The use of video performance analysis software to measure an improvement in interprofessional collaboration as a result of high fidelity ward simulation education. (2nd November 2015) - Harris, Patrick; Walker, Wendy; Kilkie, Sharon; Spence, Chloe; Gavin, Cathy
Abstract : Background: Delivering safe and effective care is both challenging and essential within the modern healthcare setting. 1 There is strong evidence to support the links between patient experience of care and safety. 2 The opportunity to develop learning across professions and to improve work opportunities and retention of staff within the local area is a strategic priority 3 and interprofessional education (IPE) is recognised as a key to the delivery of safe and effective healthcare. 4 Methodology: A simulation-based workshop was designed to focus the learners on improved understanding of the roles, contributions and expectations of a multi-professional team in the context of patient safety. A team of doctors, nursing staff and allied therapists were asked to manage a ward of 4 patients (live actors) for a period of 40 mins during which all care was to be given. Each patient had general and specific needs and the ward was seeded with safety issues. Simulation was debriefed exploring: what extra information they would need to enable them to do their job; what their roles/responsibilities were in the safe management of the patients; how they would improve the management of the scenario if asked to again. The simulation was then re-run. Each simulation was videoed and analysed for evidence of the time taken to initiate inter professional collaboration and its frequency using StudioCode software. 5 Results/outcomes: Pre- and post-workshop questionnaires using a Validating the Readiness for Interprofessional Learning Scale (RIPLS) 6 and video analysis measured interprofessional collaboration. Interim quantitative and qualitative analysis suggests a reduction in time to first episode of interprofessional collaboration between simulation one and two, increased frequency of IP communication episodes and a reduction in time to complete the task releasing time for debriefing. Conclusions and recommendations: High fidelity can be used to improve interprofessional collaboration. References: Leonard M, Graham S, Bonacum D. Qual Saf Health Care. 2004;13:85–90 National Quality Board. Improving experiences of care . 2015 Health Education West Midlands Staffordshire and Shropshire LETC Workforce Development Plan, 2013 Parliamentary and Health Services Ombudsman. Listening and Learning: The Ombudsman's review of complaint handling by the NHS in England 2011–2012, 2012 Studiocode Group Sydney Australia Reid R, Bruce D, Allstaff K, McLernon D. Validating for readiness for interprofessional learning scale (RIPLS) in the postgraduate context: are health care professionals ready for IPL? Med Educ. 2006;40:415–422